Pilot study assessing the use of cabergoline for the treatment of cats with hypersomatotropism and diabetes mellitus. Issue 2 (February 2021) - Scudder, Christopher J; Hazuchova, Katarina; Gostelow, Ruth; Church, David B; Forcada, Yaiza; Fowkes, Robert C; Niessen, Stijn JM
Objectives: An affordable and effective treatment is needed to manage feline hypersomatotropism. The aim of this study was to assess whether treatment with oral cabergoline for 90 days in cats with hypersomatotropism and diabetes mellitus improved diabetic and insulin-like growth factor 1 (IGF-1) control. Methods: This was a prospective cohort non-blinded pilot study enrolling client-owned cats with spontaneously occurring diabetes mellitus and hypersomatotropism. Cats received oral cabergoline (5–10 µg/kg q24h) for 90 consecutive days. Serum IGF-1 and fructosamine concentrations were measured on days 1, 30 and 90. Quality of life was determined using the DIAQoL-pet questionnaire on days 1 and 90. Results: Nine cats were enrolled and eight completed the study. There was no significant change in the following: IGF-1 (day 1 median 2001 ng/ml [range 890–2001 ng/ml]; day 30 median 2001 ng/ml [range 929–2001 ng/ml]; day 90 median 1828 ng/ml [range 1035–2001 ng/ml]; χ 2 (2) = 0.667, P  = 0.805); fructosamine (day 1 median 499 µmol/l [range 330–887 µmol/l], day 30 median 551 µmol/l [range 288–722 µmol/l], day 90 median 503 [range 315–851 µmol/l]; χ 2 (2) = 0.581, P  = 0.764); or DIAQoL-pet score (median on day 1 –2.79 [range –4.62 to –0.28], median on day 90 –3.24 [range –4.41 to –0.28]; P  = 0.715). There was a significant change of insulin dose (χ 2 (2) = 8.667, P  = 0.008) with cats receiving higher insulin doses at day 90 compared with day 1 (median on day 1 was 0.98 [range 0.63–1.49] and median on day 90 was 1.56 [range 0.49–2.55] units/kg q12h; P  = 0.026). Conclusions and relevance: Cabergoline did not improve diabetic control or normalise insulin-like growth factor concentration, or improve patient quality of life.